Assessment of the Digital Market in Croatia - World Bank (World Bank, Washington, DC, 2021)
With a view to supporting Croatia’s continued efforts to advance its digital transformation, this report contains the findings of a comprehensive study of the digital sector in Croatia. In this study, the digital sector is defined as the internet (fixed and mobile), telephony (fixed and mobile), and pay TV markets. The study examines indicators of Croatia’s performance relative to a set of peer countries and the European Union (EU) average, with an emphasis on fixed and mobile broadband services as foundational elements of the digital transformation. To complete the assessment, other related factors, such as human capital, the integration of digital technology into the economy, and digital public services, are also considered at a higher level. The study then identifies specific gaps pertaining to digital infrastructure as well as the regulations and policies needed for a vibrant and competitive digital sector. On the opportunities side, the study assesses the relevance of encouraging the development of four emerging technologies in Croatia: the Internet of Things (IoT); artificial intelligence (AI); data centers and cloud services; and smart cities. The report concludes with high-level strategic and actionable recommendations drawn from the analysis. In light of the three national disasters that have recently affected Croatia, namely, the Zagreb earthquake in March 2020, the December earthquakes that struck the Sisak-Moslavina County, and the outbreak of Coronavirus (COVID-19), this report also highlights the role that digital infrastructure and services could play in strengthening Croatia’s resilience to such crises.